Prediction of Isotherm Concerning Dual Competitive and Enhancing Action of Chloride Ion on Benzotriazol Adsorption on Heterogeneous Steel Surface - R. Ismaeel, A. (Asian Journal of Chemistry, 2010)
Adsorption of benzotriazol on steel surface from hydrochloric acid solutions was studied indicating decrease of corrosion inhibition effectiveness and surface coverage as hydrochloric acid concentration increases. Considering competitive action of chloride ions with benzotriazol molecules for adsorption on steel, Jaroniec adsorption isotherm for adsorption of two components of different molecular sizes on heterogeneous solids is not applicable to our results except at high benzotriazol concentrations and could not explain experimental behaviours. An adsorption isotherm concerning enhancing and competitive action of chloride ion on benzotriazol adsorption is predicted, which is applicable to and explains experimental results.